ANALYSIS OF PROBLEMS AND STRATEGIES FOR IMPROVING THE SOCIO-ECONOMIC AGRICULTURE OF LUBUK KERTANG VILLAGE, LANGKAT REGENCY - Harahap, Mailina; Siregar, Gustina; Riza, Fetra Venny (Jurnal AGRISEP, 2023)
The role of the agricultural sector is inseparable from the existence of a village which is the smallest regional unit, one of the common characteristics of which is to do business in the agricultural sector. Lubuk Kertang Village is one of the 7 Villages in the District of West Berandan, Langkat Regency, which has large development potential, even more so with the assignment of Lubuk Kertang Village as a Mangrove Forest Ecotourism area. In its development, the village was also faced with various local problems. The research method used was a participatory approach, namely the Participatory Rural Appraisal (PRA) technique. Data analysis was performed statistically descriptive and qualitative. Problems in Lubuk Kertang Village, West Brandan District, Langkat Regency include: agriculture, water, human resource capacity, economy, health, law and morals and institutions. The village problems can be overcome with the development strategy of making the village of Lubuk Kertang an Agro-tourism destination.